Dampak Pembangunan Gender terhadap Kemiskinan di Kota-Kota Besar di Indonesia Tahun 2017-2022 - Maziyyah, Fatih; Arif, Muhammad (Ekonomis: Journal of Economics and Business, 2024)
This research aims to analyze the influence of women's participation in parliament, the women's gender development index, women's per capita income and women's life expectancy on women's poverty levels in big cities in Indonesia for the 2017-2022 period. This research is quantitative research using the panel data regression method with the best model, namely the Fixed Effect Model (FEM). The results of the simultaneous significant test show that in 2017-2022 the variables Women's Participation, Women's Gender Development Index, Women's Per Capita Income and Women's Life Expectancy have a simultaneous effect on Women's Poverty Levels in big cities in Indonesia in 2017-2022. The results of the partial significance test show that the variable Women's Life Expectancy has a negative and significant effect on women's poverty in 2017-2022. Meanwhile, the variables Women's Participation, Women's Gender Development Index, and Women's Per Capita Income do not have a significant effect on women's poverty in 2017-2022.